2015
DOI: 10.4236/ajps.2015.65071
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Plant Growth Regulators on Modulating Rooting of <i>Rosa centifolia</i>

Abstract: Rosa centifolia is grown for its flowers which are used for essential oil extraction. It is vegetatively propagated through its cuttings which are difficult to root. This study was designed to increase the rooting percentage of cuttings by applying plant growth regulators (PGRs) with different levels. In total 31 treatments with different concentrations (450 ppm, 700 ppm and 950 ppm) of indole butyric acid (IBA), indole acetic acid (IAA), naphthalene acetic acid (NAA) alone, in combination and with same concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…ChristopherColombus and Vay Vicend. Similar results were reported by Akhtar et al [14] in Rosa centifoilia. Higher conc.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…ChristopherColombus and Vay Vicend. Similar results were reported by Akhtar et al [14] in Rosa centifoilia. Higher conc.…”
Section: Resultssupporting
confidence: 92%
“…when cuttings of Eiffel Tower variety were treated with IBA 500 ppm and planted during February. These results of dry weight increase in shoots are in close conformity with the work of Akhatret al [14], reports that 450 ppm IBA was effective for producing maximum shoot length, shoot dry weight, number of roots and root dry weight. The treatment of cuttings with IBA had significant effect on number of leaves per cutting (Table 3).…”
Section: Khajehpoursupporting
confidence: 92%
“…The largest number of roots in seedlings from sapling shoots was 128.67, and in crown shoots, it was 67.00. In line with the research results of [11] that there was a significant increase in the number of roots when IBA was applied to rose cuttings. Furthermore, administering auxin in solution or powder it can increase total of roots and increase opportunities success of seedlings propagated through cuttings [12].…”
Section: Total Primary Roots (100 Dap) and Root Fresh Weight (100 Dap)supporting
confidence: 88%
“…Cong (1991) also reported that Prunus triloba cuttings treated with IBA 500 ppm and planted in earthen pots containing garden soil resulted in the maximum survival of plants. Akhtar et al (2015) observed that Rosa centifolia stem cuttings of treated with IBA 450 ppm produced maximum shoot length (10.67 cm). Ficus benjamina hard wood cuttings treated with IBA at 1000 ppm take minimum days to sprouting ( Ingole et al, 2016).…”
Section: Resultsmentioning
confidence: 91%